ACCOMPLISHING THE GOALS OF A PRISON SENTENCE EXECUTED OUTSIDE OF PRISON UNDER THE ELECTRONIC SURVEILLANCE SYSTEM - Aldona Nawój-Śleszyński (Probacja)
In Poland, the penalty of imprisonment is served in prisons, and since 1 September 2009 also outside them in the electronic monitoring system. The basic purpose of serving the penalty of imprisonment in these two forms is identical, i.e. preventing a return to crime. In the literature on the subject, only some functions of this unconventional method of serving the penalty of imprisonment are currently emphasized. The author's intention is to present the most important goals and functions implemented by this untraditional form of prison isolation. Therefore, the author will try to answer the following questions: whether the introduction of the electronic monitoring system to the penitentiary system had an impact and to what extent on the reduction of the prison population, in particular short-term sentences of imprisonment, whether serving the penalty of imprisonment in the electronic monitoring system had an impact on preventing prison overcrowding, whether the prison population became denser during the COVID-19 pandemic? In addition, the author presents the problem of returning to crime after serving a sentence of imprisonment in the electronic monitoring system, which has only recently appeared in the literature. This institution has not solved many problems related to the execution of imprisonment in prison, has not influenced the radical reduction of the prison population or the increase in the postulated area of the residential cell, but it has a huge potential for resocialization, which is why directing convicts to this system of execution of imprisonment is purposeful and rational, and increasing its capacity is still a current postulate.